Perhitungan Dana Pensiun Metode Entry Age Normal Asumsi Bunga Cox Ingersoll Ross - Nuri, Sindri Delva; Rosita, Silvia; Z, Yulia Rahmawati (Jurnal Edumatika, 2024)
The payment of pension benefits is fully borne by the APBN, resulting in a drastic increase in the APBN. This can happen because it is influenced by funding calculations with inaccurate assumptions. One of the influential assumptions is the assumption of interest rates. The assumption of interest rates in calculating pension funds uses constant interest rates and does not follow the movement of the BI rate reference rate, so it is not precise because interest rates fluctuate. Therefore, in this study the Cox Ingersoll Ross stochastic interest rate pension fund model was carried out using the Entry Age Normal method. Based on a comparison of the results of the 8% constant interest rate and the CIR interest rate, it can be seen that the calculation of pension funds at the CIR interest rate, the value of normal contributions and actuarial obligations is much greater than that of the constant interest rate, so it is better for the company.